GERAKAN SALAT SUBUH BERJEMAAH (GSSB) DI KELURAHAN KEPENUHAN TENGAH KECAMATAN KEPENUHAN - Ramadhan, Suryandi; ", Jonyanis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study attempts to investigate a Congregational Subuh Prayer Movement (GSSB) in Kepenuhan Tengah Urban Village, Kepenuhan, Rokan Hulu, Riau. GSSB is an active socio-religious organisation in community’s life. It is a very agile today’s community social movement in the midst of rapid development of technological advances. GSSB has an impact on the religious behaviour of community members in Kepenuhan Tengah Urban Village. This study employs Talcott Parsons' AGIL Theory. The data were gathered through interviews, observation, and documentation, and analysed using descriptive qualitative method. The subjects were administrators of the GSSB, religious leaders, and community figures of Kepenuhan Tengah Urban Village. The results highlight that the community members of Kepenuhan Tengah Urban Village have been actively participating in the GSSB on every Sunday. The GSSB activity, which is held once a week, has been greeted enthusiastically by the congregation, especially in Kepenuhan Tengah Urban Village. The reason for the community to participate in the GSSB is due to it is an obligation for a Muslim as the religious order to perform Subuh prayer in congregation. Keywords: Congregational Subuh Prayer, Organisation, Social Behaviour